HABITAT UTILIZATION OF HIMALAYAN MUSK DEER (M OSCHUS CHRYSOGASTER) IN THE MUSK DEER NATIONAL PARK GURAIZ, AZAD JAMMU AND KASHMIR, PAKISTAN - B. D. Qureshi; M. Anwar; I. Hussain; M. A. Beg (Journal of Animal and Plant Sciences, 2013)
In Pakistan, Himalayan musk deer (Moschus chrysogaster) inhabits sub-alpine scrub, and mixed coniferous forest usually between 2785m and 4000m. We took 42 sample plots of size 10×10m for trees, 41 sample plots of 4×4m for shrubs and 42 of 1×1m for herb/grass layer to study the  priority habitat of musk deer at different aspects between 2785m-3420m elevation. Of total vegetation , trees, shrubs, and herbs/grasses contributed 40.47%, 17.35%, and 42.17% of relative frequency, respectively. Among trees, Betula utilis (IVI=53.29), Abies pindrow (IVI=49.63), Picea smithiana (IVI=33.61) and Taxus wallichiana (IVI=8.60) were dominant in the musk deer habitat. Major shrubs included Betula utilis, Viburnum grandiflorum, Rosa moschata, Rosa macrophylla and Lonicera spp. Herb/grass layer was dominated by Poa annua followed by Polygonum amplexicaule, Sambucus wightiana Viola spp., Ajuga parviflora, Saxifraga ciliata andPodophyllum  emodi. The animal showed association with Betula utilis, Abies pindrow,  Picea smithiana and Taxus baccata along with the shrubs of Skimmia laureola, and Rosa moschata. Musk deer is listed as Endangered in Pakistan.  Major threats to the population of Himalayan musk deer are habitat degradation due to deforestation and illicit livestock grazing along with illegal hunting for musk pod collection.
Keywords: Musk Deer; Guraiz; Neelum valley; Habitat preference; Threats